Community Empowerment in Processing Starfruit Into Innovative Snack Products As an Effort to Increase the Economic Value of Local Fruits - Sari, Santy Permata; Leba', Fransiska Kristina; Ragha, Martina Yasinta; Gore, Oktavianus; Dhawe, Vinsensia (Pascasarjana Universitas Mataram, 2024)
This community service aims to empower housewives in Ende Tengah Sub-district, Ende Regency, through training in processing starfruit into innovative snack products. This activity was carried out as an effort to increase the economic value of local fruits and community productivity. The method used was training and demonstration of making starfruit processed products. The results of the activity showed an increase in participants' knowledge and skills in processing starfruit into economically valuable products. This activity has the potential to increase household income and encourage entrepreneurial development based on local products